2023
DOI: 10.1002/cam4.5607
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of frontline intensification in primary CNS lymphoma: A real‐world single‐center experience

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(65 reference statements)
1
4
0
Order By: Relevance
“…Age of more than 60 years old and bilateral cerebral lesions were independent prognostic factors for PCNSL patients in this study. Our findings on the clinical features of patients with DLBCL-type PCNSL align with previous reports, including a trend towards older age and occurrence in immunocompetent individuals [ 17 , 18 ]. We compared the results with that of the IELSG 32 trial and found that patients in Taiwan with DLBCL-type PCNSL had a higher average age (63 vs. 57 years old) and a worse performance status (ECOG ≥ 2:70% vs. 33%) [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Age of more than 60 years old and bilateral cerebral lesions were independent prognostic factors for PCNSL patients in this study. Our findings on the clinical features of patients with DLBCL-type PCNSL align with previous reports, including a trend towards older age and occurrence in immunocompetent individuals [ 17 , 18 ]. We compared the results with that of the IELSG 32 trial and found that patients in Taiwan with DLBCL-type PCNSL had a higher average age (63 vs. 57 years old) and a worse performance status (ECOG ≥ 2:70% vs. 33%) [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study of 124 patients with DLBCL-type PCNSL provided real-world experience on clinical characteristics, treatment response, and outcomes. This is the largest PCNSL series reported in Taiwan [ 17 ]. Patients were mainly older adults (median age 63) with poor ECOG performance status (70.9% ECOG ≥ 2) and a median OS of 27.1 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported treatment-related mortality using intensified approaches varies with rates up to 12%. [6][7][8][9][10] Prognostic scoring systems have been developed to better riskstratify patients and assist in the selection of therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients will not respond to induction therapy, whereas a substantial proportion of them will develop relevant side effects, leading to treatment discontinuation or even death. The reported treatment‐related mortality using intensified approaches varies with rates up to 12% 6–10 …”
Section: Introductionmentioning
confidence: 99%